The relationship between motivations of volunteers and psychological well-being in Iranian elderly individuals - Zahra Sheibani; Akram Sanagoo; Fatemeh Mehravar; Leila Jouybari (Journal of Research Development in Nursing and Midwifery)
Background: Participatory actions and voluntary behaviors play a significant role in the health of elderly individuals. Evidence suggests that engagement in voluntary work positively impacts health, psychological well-being, and even longevity, with these benefits being particularly pronounced among older adults. The aim of this study was to examine the relationship between motivation for volunteer activities and psychological well-being in elderly individuals. Methods: An analytical cross-sectional study was conducted involving 496 elderly individuals, selected through a multi-stage non-random sampling method, at comprehensive health service centers in Golestan Province, Northern Iran, in 2023. Data were collected through Clary's Voluntary Activities Questionnaire and Ryff's Psychological Well-Being Questionnaire. The data were analyzed using Pearson correlation tests, independent t-tests, chi-square tests, and ANOVA by SPSS v.26, all at a significance level of 0.05. Results: The mean scores of voluntary motivation and psychological well-being among the elderly were 180.01±11.79 and 64.72±5.30, respectively. The results of the Pearson correlation test indicated a positive and significant relationship between the total score of voluntary functions and the total score of psychological well-being (r=0.1, p = 0.03). Conclusion: Motivation for volunteer activities may be a significant factor in enhancing the psychological well-being of elderly individuals. Therefore, it is essential for policymakers in elderly health to create conditions that encourage participation in voluntary activities to promote psychological well-being.